The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1128/jb.01115-09
|View full text |Cite
|
Sign up to set email alerts
|

Thermococcus kodakar ensis Mutants Deficient in Di- myo -Inositol Phosphate Use Aspartate To Cope with Heat Stress

Abstract: Many of the marine microorganisms which are adapted to grow at temperatures above 80°C accumulate di-myo-inositol phosphate (DIP) in response to heat stress. This led to the hypothesis that the solute plays a role in thermoprotection, but there is a lack of definitive experimental evidence. Mutant strains of Thermococcus kodakarensis (formerly Thermococcus kodakaraensis), manipulated in their ability to synthesize DIP, were constructed and used to investigate the involvement of DIP in thermoadaptation of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
(34 reference statements)
0
33
2
Order By: Relevance
“…Many temperature studies in the Thermotogae have focused on the accumulation of these organic compounds and polyamines and the elucidation of their biosynthetic pathways in T. maritima and the more moderate thermophile Petrotoga miotherma (Zellner and Kneifel 1993;Jorge et al 2007;Rodrigues et al 2009;Oshima et al 2011;Rodionova et al 2013). Several compatible solutes have so far been found only in thermophiles, including di-myoinositol phosphate, mannosyl-di-myo-inositol phosphate, mannosylglyceramide, and diglycerol phosphate (Borges et al 2010;Gonçalves et al 2012), and novel thermophilic solutes continue to be identified (Jorge et al 2007;Rodrigues et al 2009). However, while these compounds are thermophile-specific and may represent thermophilespecific adaptations, they are not the only compatible solutes used to deal with heat stress.…”
Section: Compatible Solutes: the Power Of Redundancymentioning
confidence: 99%
See 2 more Smart Citations
“…Many temperature studies in the Thermotogae have focused on the accumulation of these organic compounds and polyamines and the elucidation of their biosynthetic pathways in T. maritima and the more moderate thermophile Petrotoga miotherma (Zellner and Kneifel 1993;Jorge et al 2007;Rodrigues et al 2009;Oshima et al 2011;Rodionova et al 2013). Several compatible solutes have so far been found only in thermophiles, including di-myoinositol phosphate, mannosyl-di-myo-inositol phosphate, mannosylglyceramide, and diglycerol phosphate (Borges et al 2010;Gonçalves et al 2012), and novel thermophilic solutes continue to be identified (Jorge et al 2007;Rodrigues et al 2009). However, while these compounds are thermophile-specific and may represent thermophilespecific adaptations, they are not the only compatible solutes used to deal with heat stress.…”
Section: Compatible Solutes: the Power Of Redundancymentioning
confidence: 99%
“…Similarly, the compatible solute di-myo-inositol phosphate is thought to be important for heat tolerance in thermophiles and hyperthermophiles (Borges et al 2010). Two key genes involved in the synthesis of this compound (inositol-1-phosphate cytidylyltransferase and di-myo-inositol phosphate phosphate synthase) are suggested to have been laterally transferred from an archaeal lineage to hyperthermophilic marine Thermotoga species, while in other lineages the 2 genes are predicted to have fused before being exchanged among several bacterial and archaeal lineages (Gonçalves et al 2012).…”
Section: Role Of Lgt In Temperature Adaptation: Acquisition Of Alreadmentioning
confidence: 99%
See 1 more Smart Citation
“…furiosus is an ideal target organism for investigating the physiological role of MG and DIP because these are the major components of its solute pool, they are produced by de novo synthesis, and, importantly, the organism does not accumulate amino acids or other biomolecules from the external medium to cope with osmotic and heat stress (8). The preferential import of alternative solutes could complicate the interpretation of results, as reported for a DIP-deficient mutant of Thermococcus kodakarensis (15). The biosynthetic pathways of DIP and MG are depicted in Fig.…”
mentioning
confidence: 99%
“…One interesting example involved the in vivo disruption and analysis of a gene encoding reverse gyrase on the T. kodakaraensis genome, which revealed that the gene product functions in adaptation to high temperature, because reverse gyrase is highly conserved only in hyperthermophiles (Atomi et al, 2004). These efficient genetic tools have already been used to investigate several biological systems, such as the glycolysis pathway (Yoshida et al, 2006;Matsumi et al, 2007), natural product biosynthesis (Yokooji et al, 2009;Borges et al, 2010), transcription factors (Kanai et al, 2007(Kanai et al, , 2010, and operon transcription and translation machinery Hirata et al, 2008). However, these useful and powerful techniques have not yet been applied to the analysis of DNA repair.…”
Section: Introductionmentioning
confidence: 99%